Ownership structure and firm performance in Malaysia: the moderating effect of corruption risk - Marzuki, Hafizah; Hasnan, Suhaily; Mohd Ali, Mazurina; Harymawan, Iman (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2025)
The purpose of this study was to examine the effects of ownership structure on firm performance and the interaction effect of a firm’s corruption risk with the ownership structure. Data were collected from the annual reports of 280 Malaysian public listed firms over the period 2018 to 2022. Multiple regression analyses were run to assess the empirical status of the research hypotheses. For direct relationship, the results showed a positive and significant relationship between foreign ownership and firm performance, while family ownership and institutional ownership had no significant relationship with firm performance. For interaction effect, there was evidence of corruption risk having a moderating effect on the positive influence of family, foreign, and institutional ownership against firm performance. The key results of the study are beneficial to highlight the roles of family, foreign, and institutional shareholders in accelerating firm performance, even though the Malaysian business environment is vulnerable to corruption risks. The originality of this study lies on the role of corruption risk in weakening or strengthening the ownership structure-firm performance relationship. This study makes a novel contribution to business players, shareholders, academicians, professionals, policymakers, and regulators. Limitations and future directions of the study are also discussed.